2020
DOI: 10.3390/s20082421
|View full text |Cite
|
Sign up to set email alerts
|

Perception of a Haptic Stimulus Presented Under the Foot Under Workload

Abstract: It is clear that the haptic channel can be exploited as a communication medium for several tasks of everyday life. Here we investigated whether such communication can be altered in a cognitive load situation. We studied the perception of a vibrotactile stimulus presented under the foot when the attention is loaded by another task (cognitive load). The results demonstrated a significant influence of workload on the perception of the vibrotactile stimulus. Overall, we observed that the average score in the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…In the literature, one can find publications in which the results of research on determining the vibrotactile thresholds are presented, but both the measurement procedures and used devices are individually selected by scientists each time. Examples of vibrotactile detection methods are shown in the publications [ 4 , 16 , 34 ]. In the indicated publications, the measurement procedure and, in particular, the technical solutions used have not been described in detail, and the application of similar solutions could be difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, one can find publications in which the results of research on determining the vibrotactile thresholds are presented, but both the measurement procedures and used devices are individually selected by scientists each time. Examples of vibrotactile detection methods are shown in the publications [ 4 , 16 , 34 ]. In the indicated publications, the measurement procedure and, in particular, the technical solutions used have not been described in detail, and the application of similar solutions could be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Many conferences are being conducted on this subject because despite the existence of considerable knowledge, there remains much to be researched in this field; to this end, the WHC World Haptics Conference is held every two years [ 3 ]. Various parameters related to the feeling of vibrations and pressure forces are tested, such as the vibrotactile perception threshold [ 4 ] and simple reaction time and response time [ 5 ]. The described research was inspired by the design of a vibrating bracelet for blind and partially sighted people, in line with the idea of a smart city for all.…”
Section: Introductionmentioning
confidence: 99%
“…Several related studies have reported that haptic feedback improves the response time and performance [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In particular, in environments requiring visual attention such as driving, lack of haptic feedback could considerably hinder safety, making such critical feedback [ 10 , 20 , 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…23 The nature of the concomitant task affected the identification of vibrotactile messages; perception was less influenced by purely cognitive tasks, e.g., counting forwards or backward, in comparison to motor tasks, such as walking. 24 Building upon this reasoning, Mortimer and collaborators investigated different concomitant tasks, reporting that not all tasks interfered with the identification of haptic messages, speculating that tasks with high cognitive load may lead to low identification rates. 25 Engaging in multiple activities simultaneously can generally impair the performance of all involved activities due to the intrinsic limitations of the nervous system when processing concomitant information.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, auditory and visual distractors affected greatly the detection times of vibrotactile messages, and several methods (e.g., icon metaphor and family‐based design) were proposed to make haptic messages more robust 23 . The nature of the concomitant task affected the identification of vibrotactile messages; perception was less influenced by purely cognitive tasks, e.g., counting forwards or backward, in comparison to motor tasks, such as walking 24 . Building upon this reasoning, Mortimer and collaborators investigated different concomitant tasks, reporting that not all tasks interfered with the identification of haptic messages, speculating that tasks with high cognitive load may lead to low identification rates 25 .…”
Section: Introductionmentioning
confidence: 99%